IMPROVING THE LEARNING OUTCOMES OF ISLAMIC RELIGIOUS EDUCATION (IRE) ON ZAKAT, HAJJ, AND WAQF TOPICS THROUGH GROUP INVESTIGATION LEARNING METHOD - Muhsinin (Al-Hikmah: International Journal of Islamic Studies, 2025)
Group Investigation is recognized as one of the most intellectually demanding and collaborative methods within the cooperative learning paradigm, requiring students to actively engage in planning, investigating, and presenting their findings in a structured yet flexible environment. This study was conducted to examine the effectiveness of the Group Investigation method in enhancing learning outcomes in Islamic Religious Education, specifically on the topics of Zakat, Hajj, and Waqf among Grade 10 students of Science Class 4 at SMAN 1 Menganti. The research employed a Classroom Action Research (CAR) framework, implemented in two iterative cycles to ensure systematic observation, reflection, and refinement of the instructional process. Data were collected through observation, tests, and documentation to capture both cognitive achievement and student engagement. The findings indicate that the application of the Group Investigation method by the Islamic Education teacher successfully fulfilled all procedural stages, including group formation, topic selection, planning of investigations, data collection, analysis, and collaborative presentation of results. This approach not only improved students’ mastery of the subject matter but also fostered active participation, critical thinking, and cooperative skills, reflecting the integrative nature of Islamic education that combines intellectual growth with moral and spiritual development. The results suggest that Group Investigation, when implemented with appropriate scaffolding and teacher guidance, can serve as an effective pedagogical strategy for deepening understanding and enhancing learning outcomes in Islamic Religious Education.